2021
DOI: 10.1111/jmp.12513
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and treatment of endometriosis in a hooded capuchin (Sapajus apella)

Abstract: Spontaneous endometriosis is common in women, great apes and Old World monkeys, but rare in New World monkeys. We report on the clinical diagnosis and successful combination of surgical and medical treatment in a case of spontaneous endometriosis in a diabetic hooded capuchin. Addressing this painful condition had a positive welfare impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Behavioral changes and changes in group hierarchy are also observed with contraceptive use in certain reports (Agnew et al, 2016) but not in others (Moresco et al, 2021). This discrepancy indicates that there is much research needed to elucidate the effects that specific contraceptives, species and potentially individuals can have on social dynamics.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavioral changes and changes in group hierarchy are also observed with contraceptive use in certain reports (Agnew et al, 2016) but not in others (Moresco et al, 2021). This discrepancy indicates that there is much research needed to elucidate the effects that specific contraceptives, species and potentially individuals can have on social dynamics.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Data), gorillas (Doré & Lagacé, 1985), rhesus and cynomolgus macaques (Ami et al, 1993;Zondervan et al, 2004), baboon (Papio anubis, Papio cynocephalus, Papio papio) (Dallwig et al, 2011;D'Hooghe et al, 1991), Allen's swamp monkey (Allenopithecus nigroviridus) (Jafarey et al, 2015), DeBrazza monkey (C. neglectus) (Binhazim et al, 1989). In contrast, very few spontaneous cases have been reported in NTM (Cowl et al, 2018;David et al, 2009;Moresco et al, 2021), and no reports were found in the literature for prosimians.…”
Section: Uterine Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In the article by Moresco et al, 1 the brand of the product ‘(9.4 mg, Suprelorin®, Zoetis)’ was incorrect on page 147 and it should read as ‘(9.4 mg, Suprelorin®, Virbac).’…”
mentioning
confidence: 99%